Construction of a cDNA Library of Vitis pseudoreticulata Native to China Inoculated with Uncinula necator and the Analysis of Potential Defence-related Expressed Sequence Tags (ESTs) - Xu, Y.; Zhu, Z.; Xiao, Y.; Wang, Y. (South African Journal of Enology and Viticulture, 2016)
Expressed sequence tags (ESTs) constitute a rapid and informative strategy for studying the gene expression profiles of specific stages of annual and perennial plant species. In the study undertaken for this report, a cDNA library was constructed from the young leaves of Chinese wild Vitis pseudoreticulata inoculated with Uncinula necator (Schwein.) Burrill. The leaves were harvested at various times after inoculation for total RNA extraction, which was used to generate ESTs. In our study, 107 cDNA clones were sequenced from either the 5’ or 3’ end of the cDNAs. Of these, 60 unigenes (56.1%) were functionally characterised by the BLASTX matches to known-function proteins, and 20 unigenes (18.7%) matched significantly with proteins with unknown function in the public databases. The remaining 27 unigenes (25.2%) failed to show significant homology to any proteins in the public databases, suggesting that they represented novel sequences. Some functional genes identified from the cDNA library and their potential with plant defence system is discussed.